2022
DOI: 10.1002/jsfa.12177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal process on the key aroma components of green tea with chestnut‐like aroma

Abstract: BACKGROUND: Chestnut-like aroma is one of the unique qualities of Chinese green tea and has become an important factor influencing consumer decisions. However, the chemical formation mechanism of chestnut-like aroma during green tea processing remains unclear. In this study, the dynamic changes of key components contributing to chestnut-like aroma and their precursors were analyzed in fresh leaves, fixation leaves, first baking tea leaves, and green tea.RESULTS: The thermal process had an important effect on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…For example, β-ionone is a common active odorant in green tea varieties and it is associated with the intensity of floral and sweet aromas [57,58]; however, it was negatively correlated with the floral scents in this study (Figure 6B). Jasmone, geranylacetone, and D-limonene are key odorants responsible for the chestnut-like aroma of green tea [59,60]. Unlike previous studies, this study found that geranylacetone had a very high OAV in all three types of HSGT, and the correlation analysis revealed that it was positively correlated with the roasted flavor (Figure 6B).…”
Section: Geranylacetone β-Ionone Indole Nerolidol and Dihydrolinalool...contrasting
confidence: 70%
“…For example, β-ionone is a common active odorant in green tea varieties and it is associated with the intensity of floral and sweet aromas [57,58]; however, it was negatively correlated with the floral scents in this study (Figure 6B). Jasmone, geranylacetone, and D-limonene are key odorants responsible for the chestnut-like aroma of green tea [59,60]. Unlike previous studies, this study found that geranylacetone had a very high OAV in all three types of HSGT, and the correlation analysis revealed that it was positively correlated with the roasted flavor (Figure 6B).…”
Section: Geranylacetone β-Ionone Indole Nerolidol and Dihydrolinalool...contrasting
confidence: 70%
“…Meanwhile, three volatile compounds, 1,3-Diethylbenzene, 1,4-Diethylbenzene and Naphthalene, exhibited higher emission in BR-S-10. These volatile compounds described above are also found in other plant species (Zhang et al, 2019;Koner et al, 2022;de Paula et al, 2023;Qu et al, 2023). For example, 2,4-Dimethylstyrene has been identified as an aroma compound in mango and a key odorant responsible for the chestnut-like aroma of green tea (Zhang et al, 2019;Qu et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…These volatile compounds described above are also found in other plant species (Zhang et al, 2019;Koner et al, 2022;de Paula et al, 2023;Qu et al, 2023). For example, 2,4-Dimethylstyrene has been identified as an aroma compound in mango and a key odorant responsible for the chestnut-like aroma of green tea (Zhang et al, 2019;Qu et al, 2023). It is well established that cotton plants damaged by piercing-sucking hemipterans, such as A. lucorum, undergo both quantitative and qualitative changes in their volatile emissions (Williams et al, 2005;Huang et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Due to their low cytotoxicity and low side effects, herbs with a wide range of pharmacological activities are of increasing interest in the treatment of human diseases, including asthma. Extensive studies over the past few decades have shown that α-terpineol, a monocyclic terpene widely found in various plants and foods, such as citrus fruits, 26 green tea, 27 pomegranate, 28 eucalyptus 29 and cabbage-stalk, 30 has a variety of pharmacological properties, especially the anti-inflammatory effect. However, the potential protective effect of α-terpineol in alleviating asthma remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%